Dialogue on U.S.-Vietnam Relations DOMESTIC DIMENSIONS - Jonathan R. Stromseth; Jonathan R. Stromseth (2003)
This report is part of a broader research and publication project on U.S.-Vietnam relations being conducted by The Asia Foundation in cooperation with Vietnam ’s Institute for International Relations (IIR), with funding support from the Henry Luce Foundation. The project supports research activities that examine domestic and international factors affecting the bilateral relationship,especially in the context of economic normalization between the two countries and a changing international environment in the Asia-Pacific region. Ultimately, it aims to promote greater understanding among Americans and Vietnamese about domestic conditions and international factors that affect bilateral relations,leading to more informed policy making on both sides.